On Syntactic Integration and Semantico-Pragmatic Distribution of Mbya Guarani Purpose Coding Strategies - Baranger, Estefania (2022)
The aim of this paper is to describe the available strategies for coding purpose relations in Mbya, focusing on their semantico-pragmatic distribution. According to Dooley, Mbya Guarani presents two main different strategies involved in the coding of purpose relations: aguã nominalizations and vy-dependent clauses, and among the latter a motion-cum-purpose (MCP) construction subtype is included. These strategies differ in regard to the semantic class of the main verb, referential continuity between the dependent and the main unit, and the fact that the dependent form can be negated independently from the main clause—thus, establishing different degrees of integration within the main unit in each case—, but overlap in same-subject contexts that involve a directed motion verb. However, according to our data, speakers do not use these constructions interchangeably, whereas aguã nominalizations portray an intended hypothetical outcome of the event or state-of-affair (hereafter SoA) expressed in the matrix clause; vy-dependent clauses and motion-cum-purpose constructions consistently trigger a result interpretation, entailing that the intended SoA was successfully accomplished.